Virtualization of Digitalized Cultural Assets to Promote Sustainable Heritage Tourism in Malaysia - Hajiedah Fauzi; Harlina Md Sharif; Rajabi Abdul Razak (International Journal of Environment, Architecture, and Societies, 2022)
A key policy goal for every nation is to ensure that their rich cultural treasures are preserved for future generations to enjoy and be inspired. In this regard, the virtualization of digitalized cultural assets has the potential to make heritage experienced in a new and unique way. However, as the guardian of the nation’s cultural assets, the museum sector in Malaysia was caught unprepared when it experienced a 70 percent dip in the attendance of visitors during the pandemic due to its inability to capitalize on technology and reach out to local and international visitors. Thus, the study’s primary objective is to assess the technology readiness level in Malaysian museums in adopting virtual heritage technologies. However, this paper explicitly discusses the challenges and methods of virtualization in museums by reviewing available literature and case studies of museums with interactive technology to understand the current technology state of museums in Malaysia. Consequently, working terminologies related to virtual heritage adoption by museums will be elaborated to define the scope and limitations of such studies. Most museums identified with Augmented Reality applications in Malaysia are still in an early stage of virtual technology adoption. Only Borneo Cultural Museum has embraced 30% interactive exhibition. Thus, this paper suggests that an in-depth study needs to be conducted to survey the technology readiness of museums in Malaysia.